Redox Reaction in the Cyclization-aromatization of (R)-(+)-Citronellal with FeCl3/Acetic Anhydride - Edy Cahyono; Muchalal Muchalal; Harno Dwi Pranonowo (EKSAKTA: Journal of Sciences and Data Analysis, 2010)
The effects of temperature, time of reaction, and the reactants mole ratio on the cyclization-acetylation of (R)-(+)-citronellal with FeCl3/acetic anhydride were studied.  Isopulegyl acetate (IPA) and neoisopulegyl acetate (NIPA) were obtained as the main products at room temperature (mole ratio of citronellal: acetic anhydride: FeCl3 = 6:12:1). Both products are relatively fixed after the 30th minute. The average concentration of IPA at 30-180 minutes was 44.71%, while the average concentration of NIPA was 28.47%. Increasing temperature (80 oC) and the amount of acetic anhydride (mol ratio 2:6:1) gave p-cymene (17.53%) and citronellyl acetate (11.31%). Autoredoks reaction on the transformation of citronellal into p-cymene and citronellyl acetate was studied with the carbon oxidation number concept. Key words: (R )-(+)- citronellal, cyclization-aromatization, FeCl3,  p-cymene, redox